Microstructure of fibres pressure-spun from polyacrylonitrile–graphene oxide composite mixtures. (8th September 2020) - Amir, Amalina; Porwal, Harshit; Mahalingam, Suntharavathanan; Wu, Xiaowen; Wu, Tongfei; Chen, Biqiong; Tabish, Tanveer A.; Edirisinghe, Mohan
Abstract: Suspensions containing 8 and 10 wt% polyacrylonitrile (PAN) and 1, 2, 3, 5, 7 and 10 wt% graphene oxide (GO) were prepared using a special mixing routine and fibres were generated from these mixtures by pressurised gyration. The combination of pressure and gyration speed was effective in controlling the fibre morphology and fibre diameter which ranged from 1 to 20 μm. Fibres were pyrolysed to remove the polymer and only the 10 wt% PAN fibres survived. The microstructure of the pre- and post-pyrolysis products were characterised by scanning electron microscopy, both with and without focussed ion beam etching, Fourier-transformed infrared and Raman spectroscopies. Pyrolysed fibre electrical conductivities were measured and only those containing 1 and 2 wt% GO were conductive.